2005
DOI: 10.1051/0004-6361:20042274
|View full text |Cite
|
Sign up to set email alerts
|

A search for very active stars in the Galaxy

Abstract: Abstract. We report the first results of a systematic search near the plane of the Galaxy for so-called very active stars (VAS), which are characterized by a hard X-ray spectrum and activity in the radio domain. Candidates with hard X-ray binary-like spectra have been selected from the Bright ROSAT Source Catalogue in the Zone of Avoidance (|b| < 20• ) and were tentatively identified in GB6/PMM/NVSS radio surveys. Most of them were observed with the ATCA and VLA. Precise radio coordinates have led to unambiguo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
2
13
0
Order By: Relevance
“…This source also has a counterpart in the XMMSlew catalogue (XMMSL1 J135340.5−663958) which provides a restricted error box, a secure identification with VASC J1353−66 and a 0.2–12 keV flux of 3.9 × 10 −12 erg cm −2 s −1 . Tsarevsky et al (2005) report that this source has a featureless optical spectrum and a flat radio spectrum which together with the detected X‐ray and radio emission leads these authors to suggest that it is probably a new BL Lac type object behind our galaxy despite the marginal detection of a small proper motion.…”
Section: The Individual Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…This source also has a counterpart in the XMMSlew catalogue (XMMSL1 J135340.5−663958) which provides a restricted error box, a secure identification with VASC J1353−66 and a 0.2–12 keV flux of 3.9 × 10 −12 erg cm −2 s −1 . Tsarevsky et al (2005) report that this source has a featureless optical spectrum and a flat radio spectrum which together with the detected X‐ray and radio emission leads these authors to suggest that it is probably a new BL Lac type object behind our galaxy despite the marginal detection of a small proper motion.…”
Section: The Individual Sourcesmentioning
confidence: 99%
“…Flat spectrum sources are those with a ≥−0.5 Only four (1FGL J0137.8+5814, 1FGL J2056.7+4938, 1FGL J2329.2+3755 and 1FGL J1926.8+6153) of the 30 ROSAT sources had information about the spectral slope in the Specfind data base and all were found to have a flat radio spectrum. Indication of a flat spectrum in other sources can be found in the literature (Reich et al 2000; Ribó et al 2002; Tsarevsky et al 2005; Jackson et al 2007; Mahony et al 2010a; Landi et al 2010) or from archival radio data [taken from HEASARC and/or NASA/IPAC Extragalactic Data base (NED)]; when available a radio loudness indication is also reported in the discussion of each individual source. The ROSAT flux, calculated in the 0.1–2.4 keV band, has also been estimated and listed in Table 2.…”
Section: Searching For Counterparts Of Unidentified Fermi Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 1FGL J1910.9+0906 (associated with the SNR G043.3−00.2; Mezger et al 1967) was not considered, nor was 1FGL J1227.9−4852 (the possible γ-ray counterpart of the atypical low-mass X-ray binary XSS J12270−4859; de Martino et al 2010Martino et al , 2013, along with the confirmed BL Lacs 1FGL J1353.6−6640 and 1FGL J1942.7+1033 (both observed with the ESO 8-m Unit 2 "Kueyen" of the Very Large Telescope by Tsarevsky et al 2005).…”
Section: The Selected Samplementioning
confidence: 99%
“…To complete the information about the Fermi-ROSAT sample of Stephen et al (2010), we also retrieved from the ESO data archive 2 the relevant files concerning optical spectroscopy of the counterparts of sources 1FGL J1353.6−6640 and 1FGL J1942.7+1033 (also in this case, these two objects are not reported in Table 1; we refer the reader to Tsarevsky et al 2005, for details about the corresponding observational setup) and reduced them independently. In total we analyzed the spectra of 28 optical objects connected with 27 Fermi-ROSAT associations from Stephen et al (2010).…”
Section: The Selected Samplementioning
confidence: 99%